Identification of an epiphytic diatom on Nitzschia sigmoidea (Bacillariophyceae). Issue 2 (3rd April 2019) - Roubeix, Vincent; Chalié, Françoise
ABSTRACT: Epiphytism on benthic motile diatoms is not common and can be considered a phoretic habitat. Nitzschia sigmoidea is a very long diatom which often exhibits epiphytes on its frustule. It was found abundantly in a small regulated stream in Provence and about half of the individuals had a variable number of adnate epiphytes on them. Examination of fresh material under a scanning electron microscope revealed that the epiphytes were diatoms belonging to the species Fallacia helensis . This species had not been reported as epiphytes on other diatoms before. More research is needed to understand the relationship between the two species and, more generally, to investigate phoretic epiphytism as an original biotic interaction between diatoms. Graphical Abstract: